Application of Queuing Theory to Patient Satisfaction at Private HospitalsDuring the Second Wave of Covid 19 - Ms ShivaliShrivastava, Dr SaloniSrivastava, Dr VipinSolanki, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The second wave of COVID-19 in India has had severe consequences in the form of spiraling cases, reduced supplies of essential treatments, and increased deaths particularly in the young population. Understanding why the second wave has been more dangerous than the first could help to identify the potential areas of diagnostics to target with future control strategies. Studies have identified various circulating double-mutant and triple-mutant strains of SARS-CoV-2 across different regions of India, which are more pathogenic than the initial strains. Such altered transmissibility and pathogenicity indicates evolution of the virus. Here we study with the help of multi-server finite length queue model at what situation they are not able to get immediate treatment and have to face their deaths and also how rapidly the problem increases. We consider all the private hospitals of Agra as multiple servers and then study the whole scenario and realized that how the condition comes at its worst state.